Pendidikan Kesehatan Anak: Pengenalan Penyakit Umum di Sekolah Dasar Wilayah Puskesmas Labuhan Sumbawa - Nur Arifatus Sholihah; Asri Reni handayani; Herni Hasifah; Hamdin Hamdin (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The low level of understanding among elementary school students regarding common diseases and their prevention can increase the risk of both communicable and non-communicable diseases from an early age. Therefore, effective health education efforts are essential to instill healthy habits in children. This community service activity aimed to improve the knowledge of elementary school students in the working area of Labuhan Sumbawa Public Health Center about common diseases and preventive measures through an interactive educational approach. The methods used included health counseling with visual media, engaging educational games, and small group discussions to encourage active participation. The activity was conducted in June 2025, involving 30 students from two elementary schools selected purposively. The educational content focused on dengue fever, diarrhea, influenza, helminthiasis, and acute respiratory infections (ARI), along with prevention strategies such as maintaining personal hygiene, consuming nutritious food, and the importance of immunization. Evaluation was carried out through pre-test and post-test assessments to measure the improvement in students’ understanding. The results showed a significant increase in students’ knowledge of the delivered material. Additionally, students demonstrated high enthusiasm and active involvement during the sessions, particularly in the educational games. These findings indicate that an interactive educational approach is effective in enhancing students’ understanding of disease prevention. This program is expected to serve as a model for sustainable health education in other elementary schools to prevent diseases from an early age and support the implementation of clean and healthy living behaviors within the school environment